Gerald Carson papers - Carson, Gerald
Correspondence, lectures and speeches, writings, research materials, and scrapbooks, pertaining to Carson's career as an advertising executive and to his research and publications in American social history. Includes a printed letter (1866) by the daredevil performer Jean François Gravelet Blondin.
Advertising industry executive, social historian, and author. Full name: Gerald Hewes Carson. Born 1899; died 1989.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blondin, -- 1824-1897.; Advertising; Social history; United States -- History; Advertising executives; Authors; Historians